2010
DOI: 10.1200/jco.2010.28.15_suppl.9024
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomized, double-blind, placebo-controlled study of pilocarpine for vaginal dryness: NCCTG study N04CA.

Abstract: Purpose-Vaginal dryness is a common problem, for which effective and safe non-estrogenic treatments are needed. Based on preliminary promising data that pilocarpine attenuated vaginal dryness, the current trial was conducted.Methods-A double-blind, placebo-controlled, randomized trial design was used to compare pilocarpine, at target doses of 5 mg twice daily and 5 mg four times daily, to a placebo. Vaginal dryness was recorded by patient-completed questionnaires at baseline and weekly for 6 weeks after study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A total of 55 studies were deemed eligible for inclusion ( Table 1, Supplementary material ). The approaches tested to treat vaginal atrophy and sexual dysfunction were as follows: lubricants and moisturizers (18 studies, 14 15 16 17 18 19 20 21 22 23 24 25 26 5 27 28 29 30 31 of which evaluated hyaluronic acid); phytoestrogens (14 studies); 30 32 33 34 35 36 37 38 39 40 41 42 43 44 dehydroepiandrosterone (DHEA; 8 studies); 27 45 46 47 48 49 50 51 ospemifene (5 studies); 52 53 54 55 56 vaginal testosterone (4 studies); 16 19 57 58 pelvic floor muscle exercises (2 studies); 59 60 oxytocin (2 studies); 61 62 vaginal CO 2 laser (2 studies); 63 64 lidocaine (1 study); 65 and vitamin E vaginal suppository (1 study). 66…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 55 studies were deemed eligible for inclusion ( Table 1, Supplementary material ). The approaches tested to treat vaginal atrophy and sexual dysfunction were as follows: lubricants and moisturizers (18 studies, 14 15 16 17 18 19 20 21 22 23 24 25 26 5 27 28 29 30 31 of which evaluated hyaluronic acid); phytoestrogens (14 studies); 30 32 33 34 35 36 37 38 39 40 41 42 43 44 dehydroepiandrosterone (DHEA; 8 studies); 27 45 46 47 48 49 50 51 ospemifene (5 studies); 52 53 54 55 56 vaginal testosterone (4 studies); 16 19 57 58 pelvic floor muscle exercises (2 studies); 59 60 oxytocin (2 studies); 61 62 vaginal CO 2 laser (2 studies); 63 64 lidocaine (1 study); 65 and vitamin E vaginal suppository (1 study). 66…”
Section: Resultsmentioning
confidence: 99%
“…Regarding side effects, the results for lubricants and moisturizers indicated that all adverse events (AEs) were considered mild in severity and self-limited. 14 15 16 17 18 19 20 21 22 23 24 25 26 The most common AEs were burn on the application site, discomfort on the application site, vulvovaginal pruritus, and general pruritus. The compound hyaluronic acid has been shown to be well tolerated without side effects among most patients tested.…”
Section: Resultsmentioning
confidence: 99%